Amelioration of LPS-Induced Jejunum Injury and Mucus Barrier Damage in Mice by IgY Embedded in W/O/W Emulsion - Zhaohui Wang; Ruihua Ye; Shidi Zhang; Chuanming Liu; Ke Chen; Kongdi Zhu; Pengjie Wang; Fuqing Wang; Jiaqiang Huang (Foods)
Chicken yolk immunoglobulin (IgY) is a natural immunologically active antibody extracted from egg yolk and can be used as a natural dietary supplement for the treatment of inflammation and damage to the intestines. In our study, IgY was embedded in a double emulsion (W/O/W; DE) to explore the therapeutic effect of the embedded IgY on Lipopolysaccharide (LPS)-induced jejunal injury in mice. The results showed that W/O/W-embedded IgY as a dietary supplement (IgY + DE) attenuated LPS-induced damage to mouse small intestinal structures and protected the integrity of the jejunal mucosal barrier. IgY + DE increased the amount of related transcription factors (Math1, Spdef, Elf3, and Klf4) and promoted thrush cell differentiation. IgY + DE ameliorated LPS-induced reduction in mucin quantity and markers. It promoted the expression of Muc1 and Muc2 and increased the mRNA expression levels of Muc1, Muc2, Muc3, Muc4, Muc13, and Agr2 (p < 0.05). IgY + DE increased the expression of several glycosyltransferases involved in mucin glycosylation. IgY + DE also neutralized the LPS attack on the expression of jejunal inflammatory factors IL-1β, IL-6, IL-4, and TNF-α. In conclusion, the IgY-embedded double emulsion can be used as a dietary supplement for immunotherapy to prevent LPS-induced jejunal injury in mice.